Effect of molasses mixed starter ration on the growth performance of crossbred calves (Indian Journal of Animal Production and Management, 2024)
Thirty two calves consisting of 16 Holstein Friesian crossbred (G1) and 16 Jersey crossbred (G2) were  divided into four different groups at one week of age keeping uniformity in breed and sex viz. T1: calves  fed on calf starter ration without molasses, T2: calf starter with 20 g, T3: calf starter with 40 g and T4: calf  starter with 60 g freshly mixed molasses per kg of feed. The average initial body weight in each group was almost similar. The calf starter ration was fed to calves twice daily ad libitum and soft green fodder such as  Para (Bracharia mutica), Napier (Pennisetum purpureum) and Guinea (Panicum maximum) grasses were  fed along with soft paddy straw free of choice as basal diet from second week onwards. The experimental calves were fed whole milk manually from a pail at the rate of 1/10th of the body weight till consumption to  0.5 kg calf starter ration (CP: 21% and TDN: 75%) daily. Wholesome potable water was also accessible  freely to the calves during the experimental period. The overall average body weight of calves were 47.31± 2.42, 50.56 ± 2.26, 57.63 ± 1.50 and 59.13 ± 1.71 kg at the 97 day of age and the average body weight gain were 0.232 ± 0.021, 0.267 ± 0.019, 0.347 ± 0.012 and 0.363 ± 0.013 kg during 7 to 97 days of age in T1, T2, T3 and T4 groups, respectively. There was significant (P
Keywords: Crossbred; calves; molasses; body weight; weaning